Mechanical behavior of a syntactic foam: experiments and modeling - Rizzi, E.; Papa, E.; Corigliano, A.
This paper reports the results of a research activity concerning the mechanical behavior of a syntactic foam employed as core material for sandwich composite panels. Following a purely phenomenological approach, experimental and numerical results are presented and compared at the macroscopic scale. The main features observed in the uniaxial, biaxial and Three Point Bending (TPB)tests are highlighted. A bimodulus constitutive model of the Drucker_}Prager type is chosen for modeling biaxial stress states with di_used damage. An alternative discrete crack approach is devised for the computer simulation of the (TPB)three point bending tests: the best matching is achieved for a rectangular Dugdale-type cohesive law. Though not proposing novel experimental or numerical methodologies, the present engineering approach should interest readers generally involved in computational composite mechanics and, speciRcally, in modeling particulate composites of the type considered here.
Keywords: COMPOSITES; SYNTACTIC FOAMS; EXPERIMENTS; UNIAXIAL TENSION/COMPRESSION; BIAXIAL COMPRESSION; THREE POINT BENDING; CONSTITUTIVE MODELS; COHESIVE LAWS; FINITE ELEMENT SIMULATIONS